Evaluasi Sistem Informasi Keuangan Perguruan Tinggi Berbasis Desktop Menggunakan Black-Box Testing dan User Acceptance Testing (UAT) - Wimmie Handiwidjojo; Lucia Dwi Krisnawati (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2026)
Transparent, accurate, and accountable financial management is essential for good university governance. However, many higher education institutions still rely on manual or semi-manual spreadsheet-based systems, leading to recording errors, reporting delays, and limited access to financial information. This community service project (PkM) aimed to improve financial governance by implementing a desktop-based financial management information system at STAK Marturia. It involved financial administrative staff, the treasurer, and the Vice Chair II for finance. The method included needs analysis, system design, and development using Visual FoxPro DBMS, and testing through Black-Box Testing and User Acceptance Testing (UAT). Black-Box Testing is used to ensure that the system’s functions comply with the specifications, while User Acceptance Testing (UAT) assesses user acceptance and the system’s ease of use. The results show that the system improved transaction recording efficiency, accelerated financial reporting, and enhanced transparency and accountability. All main functions performed well in testing, and UAT confirmed user acceptance and practical benefits. Overall, the project successfully delivered an effective IT solution to support better financial governance in higher education.